Development, Pre-Clinical Safety, and Immune Profile of RENOVAC—A Dimer RBD-Based Anti-Coronavirus Subunit Vaccine - Muzaffar Muminov; Nargiza Tsiferova; Egor Pshenichnov; Khusnora Ermatova; Oksana Charishnikova; Alisher Abdullaev; Yuliya Levitskaya; Dilbar Dalimova; Sandhya MVS; Geetanjali Tomar; Ankush Dewle; Pradhnya Choudhari; et al. (Vaccines)
Background: The development of effective and safe vaccines and their timely delivery to the public play a crucial role in preventing and managing infectious diseases. Many vaccines have been produced and distributed globally to prevent COVID-19 infection. However, establishing effective vaccine development platforms and evaluating their safety and immunogenicity remains critical to increasing health security, especially in developing countries. Objectives: Therefore, we developed a local subunit vaccine candidate, RENOVAC, and reported its toxicity and immunogenicity profile in animal models. Methods: First, the synthetic gene-coding tandem RBD linked with the GS linker was cloned into the expression vector and expressed in CHO cells. The protein was then purified and filter sterilized, and 10 µg/dose and 25 µg/dose formulations were finally examined for the 14-day repeated dose toxicity followed by the immunogenic profile in preclinical studies. Results: When administered to Sprague Dawley rats by intramuscular route, the vaccine was well tolerated up to and including the dose of 25 µg/animal, and no toxicologically adverse changes were noted. The observed change in weight of the thymus and spleen might be related to the immunological response to the vaccine. The dimer RBD vaccine demonstrated the ability to generate high levels of specific immunoglobulins (IGs) and neutralization antibodies (NAbs). Finally, changes in the amounts of specific T cells and cytokines after vaccination suggested that the vaccine mainly triggers an immune response by activating CD4+ Th2-cells, which then activate B-cells to provide humoral immunity. Conclusions: The study suggests that, based on its reliable immunogenicity and acceptable safety, the vaccine can be further directed for clinical trials.